A visual analytics framework for conservation planning optimization. (November 2021) - Zhang, Rui; Lu, Yafeng; Adams, Katherine; Sefair, Jorge A.; Mellin, Haley; Acevedo, Miguel A.; Maciejewski, Ross
Abstract: Approximately 15% of global land is currently in some state of protection. Recent conservation research suggests the need for a drastic increase of protected lands by 2050. In order to reach this target, an additional 35% of lands need to be conserved or restored in a cost-effective and time-efficient manner in order to support the resiliency of our planet and its climate. While many individuals and foundations continue raising much-needed funding for the environment, the development of conservation portfolios is a complex multi-dimensional task. Agencies have limited resources for investing in new conservation areas and have differing priorities for conservation in terms of species, land cover, human activities, etc. We present an interactive conservation portfolio development system that combines visualization, multicriteria analysis, optimization, and decision making that enables conservation planners and scientists to efficiently construct, compare, and modify conservation portfolios under multiple constraints. Highlights: Interactive decision support system for conservation planning decisions. Combines visualization, multicriteria analysis, optimization, and decision making. Multiple land portfolios can be generated and saved for comparison. New visual, analytical, and mathematical features, while allowing user interaction.